Effects of load carriage on physiological determinants in adventure racers. - Alex de O Fagundes; Elren P Monteiro; Leandro T Franzoni; Bruna S Fraga; Patrícia D Pantoja; Gabriela Fischer; Leonardo A Peyré-Tartaruga (PLoS ONE, 2017)
Adventure racing athletes need run carrying loads during the race. A better understanding of how different loads influence physiological determinants in adventure racers could provide useful insights to gauge training interventions to improve running performance. We compare the maximum oxygen uptake (VO2max), the cost of transport (C) and ventilatory thresholds of twelve adventure running athletes at three load conditions: unloaded, 7 and 15% of body mass. Twelve healthy men experienced athletes of Adventure Racing (age 31.3 ± 7.7 years, height 1.81 ± 0.05 m, body mass 75.5 ± 9.1 kg) carried out three maximal progressive (VO2max protocol) and three submaximal constant-load (running cost protocol) tests, defined in the following quasi-randomized conditions: unloaded, 7% and, 15% of body mass. The VO2max (unload: 59.7 ± 5.9; 7%: 61.7 ± 6.6 and 15%: 64.6 ± 5.4 ml kg-1 min-1) did not change among the conditions. While the 7% condition does neither modify the C nor the ventilatory thresholds, the 15% condition resulted in a higher C (5.2 ± 0.9 J kg-1 m-1; P = 0.001; d = 1.48) than the unloaded condition (4.0 ± 0.7 J kg-1 m-1). First ventilatory threshold was greater at 15% than control condition (+15.5%; P = 0.003; d = 1.44). Interestingly, the velocities on the severe-intensity domain (between second ventilatory threshold and VO2max) were reduced 1% equivalently to 1% increasing load (relative to body mass). The loading until 15% of body mass seems to affect partially the crucial metabolic and ventilatory parameters, specifically the C but not the VO2max. These findings are compatible with the concept that interventions that enhance running economy with loads may improve the running performance of adventure racing's athletes.